A facile strategy to fabricate glucose-responsive vesicles via a template of thermo-sensitive micelles. Issue 20 (28th May 2015) - Yang, Hao; Ma, Rujiang; Yue, Jing; Li, Chang; Liu, Yong; An, Yingli; Shi, Linqi
<x xml:space="preserve">Abstract</x> Polymer vesicles fabricated based on the complexation between PBA- and GA containing block copolymers exhibited glucose-responsiveness at physiological pH.